The Influence of Organizational Culture on Employee Performance at CV. Putra Lingga Jaya Sumedang - Herdiana, Agung; Sumiati, Ai; Yuniardanni, Annisya; Setiawati, Tita; Az Zahra, Syifa Aliefya (Journal of Bussines Management Basic, 2024)
The essence of the problem in this research is the low performance of employees, in which there are still employees who feel less satisfied at work causing a lack of understanding and good implementation of organizational culture at CV. Putra Lingga Jaya Sumedang which is a company in the furniture industry. The purpose of this research is to find out how much influence organizational culture has on employee performance. The method used in this research is a quantitative research method with a total of 31 respondents. The sampling technique was carried out using saturated sampling. The results of the research show that the value for the organizational culture variable obtained a score of 1,297 in the good category, while the assessment for the employee performance variable obtained a score of 1,286 in the good category. The results of simple linear regression obtained Y = 10.029 + 0.752X and the t test results tcount > ttable amounting to 9.062 > 2.045 with a significance value of 0.000 < 0.05. The relationship between organizational culture and employee performance is 0.860 at a very strong level. organizational culture on employee performance obtained a value of 73.9 while the remaining 26.1% was influenced by other factors not discussed in this research. The conclusion is that organizational culture and employee performance at CV. Putra Lingga Jaya Sumedang has been running well and according to expectations, so that organizational culture has a significant influence on employee performance